PowerPoint 2013 - Wood, William Computer software professional (Indianapolis, IN John Wiley & Sons, Inc, 2013)
Provides clear, step-by-step instructions for tackling more than 190 PowerPoint 2013 tasks. Each task-based spread covers a single technique, sure to help you get up and running on PowerPoint 2013 in no time
Starting with PowerPoint basics -- Navigating PowerPoint -- Changing PowerPoint options -- Writing and formatting text -- Working with layouts -- Organizing slides -- Working with outlines -- Using themes -- Using masters -- Adding graphics and drawings -- Enhancing slides with action -- Incorporating media -- Finalizing a slide show -- Printing presentations -- Presenting a slide show -- Publishing a presentation
Includes index
1
Keywords: Microsoft PowerPoint (Computer file); Business presentations -- Computer programs; Presentation graphics software